PEMILIHAN SAMPAH DI ITERA 2023: MEMBANGUN BUDAYA LINGKUNGAN BERSIH DAN BERKELANJUTAN - Saputra, Iwan Syahjoko; Sedo Putra, Muhammad Hakiem (TeknoKreatif: Jurnal Pengabdian kepada Masyarakat, 2025)
The community service programme entitled ‘Waste Sorting in ITERA 2023: Building a Culture of Clean and Sustainable Environment’ aims to increase awareness and participation of ITERA academic community in effective and environmentally friendly waste management. This activity was motivated by the increasing volume of waste in the campus environment and the need for more structured waste management to support the sustainability of the ecosystem. Through an educational approach and direct action in the field, this programme educates students, staff, and the surrounding community about the importance of sorting organic and inorganic waste, as well as waste utilisation through recycling and composting. The results showed that there are many variations of waste generated by the academic community on the ITERA campus. In addition, this program succeeded in analysing the amount of waste generated by the ITERA campus as well as increasing the awareness of students as the younger generation of the potential of waste and the importance of processing waste more wisely. With the success of this programme, ITERA is expected to become a role model for other educational institutions in terms of environmental management and waste reduction.